Costs associated with multidrug-resistance in inpatient palliative care - Adelhardt, Thomas; Hessemer, Stefanie; Heckel, Maria; Herbst, Franziska A.; Stiel, Stephanie; Ostgathe, Christoph; Schöffski, Oliver (Gesundheitsökonomie und Qualitätsmanagement, 2019)
The study deals with the financial impact of the occurrence of multidrug-resistant pathogens on a palliative care unit of a German university hospital. Aims of the study are an analysis of the cost drivers as well as a cost comparison between MDRO-positive and -negative patients.
CRIS-Team WoS Importer:2019-09-17